Characterization of biomass sorghum for copper phytoremediation: photosynthetic response and possibility as a bioenergy feedstock from contaminated land - Lima, Letícia Rigonato; Silva, Higor Ferreira; Brignoni, Alcindo Souza; Silva, Fabiano Guimarães; Camargos, Liliane Santos [UNESP]; Souza, Lucas Anjos (Springer Nature, 2019)
In order to decrease the concentration of toxic metals in contaminated lands, phytoextraction can be suitable considering the use of plant species with high potential for biomass production, such as biomass sorghum (Sorghum bicolor L.). We assessed a biomass sorghum (BRS716) potential as a copper phytoextractor as well as the physiological stability under this stressful condition. A completely randomized experimental design was used for a greenhouse experiment in which sorghum plants were submitted to a range of Cu 2+ concentrations: 2.3, 10.9, 19.6, 30.5, 37.6 and 55.6 mg dm −3 . The plant growth was not affected by increasing Cu 2+ concentrations, suggesting that this species is tolerant to copper. There was a decrease in photosynthetic rate according to the increase in Cu 2+ concentration, but not at a level that could disturb plant metabolism and eventual death. The values obtained for transfer index ranged from 0.62 to 0.11 which evidenced the restriction of Cu 2+ transport to the aerial parts. The more Cu 2+ available in soil, the smaller the amount of Cu 2+ transported to aerial parts of sorghum. So, our results show that biomass sorghum has potential to be used for Cu 2+ phytoextraction in concentration of up to 20 mg dm −3 . Also, in heavily Cu 2+ polluted sites, it can be used to produce biomass for bioenergy purpose, promoting a low rate of Cu 2+ extraction.
Keywords: Bioenergy; Clean technology; Environmental protection; Photosynthesis; Plant production; Toxic metals